Efficacy and Safety of Letermovir for Cytomegalovirus Prophylaxis Following Allogeneic Hematopoietic Stem Cell Transplantation in Pediatric Patients - Zhu Y; Wang L; Xiang Y; Wang Y; Zhang A; Wang Y; Yin M; Dun J; Xu Y; Hu Q; Yu W; Liu A (Drug Design, Development and Therapy, 2025)
Yongbing Zhu,* Li Wang,* Yu Xiang, Yaqin Wang, Ai Zhang, Yao Wang, Mengmeng Yin, Jianxin Dun, Yuting Xu, Qun Hu, Wen Yu,* Aiguo Liu* Department of Pediatrics, Tongji Hospital of Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Aiguo Liu, Department of Pediatrics, Tongji Hospital of Tongji Medical College, Huazhong University of Science and Technology, No. 1095 Jiefang Avenue, Wuhan, Hubei, 430030, People’s Republic of China, Tel +008627-96969985, Email drliuaiguo@tjh.tjmu.edu.cn Wen Yu, Department of Pediatrics, Tongji Hospital of Tongji Medical College, Huazhong University of Science and Technology, No. 1095 Jiefang Avenue, Wuhan, Hubei, 430030, People’s Republic of China, Email yuwen_email@163.comPurpose: Cytomegalovirus (CMV) infection represents a severe complication following hematopoietic cell transplantation (HCT), resulting in high mortality. The prevention of CMV reactivation is crucial for enhancing patient prognosis post-HCT. Letermovir prophylaxis has effectively reduced the incidence of clinically significant CMV infection (csCMVi) in adult HCT recipients. However, clinical data in pediatric patients remain limited.Patients and methods: We included 106 children who underwent HCT at our hospital between March 2019 and July 2024. The patients were grouped based on whether or not they received letermovir prophylaxis. By analyzing their general characteristics and laboratory findings, exploring the risk factors of csCMVi, and assessing the efficacy and safety of letermovir in pediatric patients.Results: Among the 106 patients, all patients were at high risk for CMV reactivation. Forty-four received letermovir prophylaxis, while 62 did not. CsCMVi occurred in 45 patients, with a significantly lower incidence in the letermovir group compared to the control group (5 [11.3%] vs 40 [64.5%], p < 0.001). Umbilical cord blood (UCB) was used in 7 patients (15.9%) in the letermovir group and in 1 patient in the control group (p < 0.05). There was no statistically significant difference in all-cause mortality between the two groups. Grade II–IV GvHD and the use of letermovir were associated with csCMVi, with letermovir identified as the only independent preventive factor for csCMVi during the first 100 days post-HCT, especially in patients with 4– 5 risk factors of csCMVi. In patients with aplastic anemia, the incidence of csCMVi was notably lower in those who received letermovir prophylaxis. No patients in the study withdrew from treatment due to adverse reactions.Conclusion: Letermovir is both effective and safe for CMV prophylaxis in pediatric patients following HCT, especially in patients with more risk factors of csCMVi. Grade II–IV GvHD increases the risk of csCMVi, while letermovir prophylaxis reduces the risk.Keywords: letermovir, pediatric, cytomegalovirus prophylaxis, hematopoietic cell transplant